Depresión, Ansiedad y Estrés durante la pandemia por Covid-19 en los estudiantes de la Unidad Educativa Saraguro - Espinosa Cañart, Carolina Stefania (2023)
The confinement due to the COVID-19 pandemic has undoubtedly caused a great impact on mental health, mainly in vulnerable people, including the youth population. Given that adolescence is a stage of socio-affective and behavioral changes, characterized by high emotional reactivity, it is important to address the problem. The main objective of this research was to determine depression, anxiety and stress in the students of the Saraguro Educational Unit during the COVID-19 pandemic, as well as to know the sociodemographic characteristics of the students; establish their levels of depression, anxiety and stress during the COVID-19 pandemic, and also promote actions for satisfactory mental health. For this, a non-experimental, cross-sectional, descriptive methodology was used, which allowed identifying levels of anxiety and depression, which were the most identified disorders. One in 28 students presented depression; The moderate level turned out to be the most frequent. Extremely severe levels of anxiety and stress affected the population studied. Finally, concluding that the majority of students show moderate levels of depression, followed by anxiety and stress, however, a minimal part of the population presents levels of extreme severity